Evaluating Maize Varietal Susceptibility and Insecticide Efficacy against Fall Armyworm - Adhikari, Chiran; Tiwari, Sundar; Thapa, Resham Bahadur; Neupane, Saraswati (Journal of Agriculture and Forestry University, 2026)
The fall armyworm (FAW), Spodoptera frugiperda (J. E. Smith, 1797) (Lepidoptera: Noctuidae), is one of the most destructive polyphagous pests, causing significant reductions in maize yield as its larvae feed on developing maize leaves and cobs. Field experiments were conducted to assess the extent of damage and yield loss caused by fall armyworm infestation in maize, following a randomized complete block design with three replications at the National Maize Research Program in Rampur, Chitwan, Nepal, during the spring season of 2023. Maize varieties such as Rampur Hybrid (RH)-10, RH-12, RH-4, RH-6, TX-369, Arun-2, ZM-401, ZM-627, BGBY POP, and Rampur Composite were used as test varieties (first factor). Pest control conditions (spray and non-spray) served as the second factor. Spray plots were treated with spinosad 45% EC, while non-spray plots received only water spray. Both were applied at 10-day intervals from the V4 stage of maize. Arun-2 was the most susceptible to fall armyworm damage, resulting in a higher pest infestation. Meanwhile, RH-12 exhibited a lower plant infestation. Quantitative yield loss increased with fall armyworm infestation, ranging from 5.54% to 34.48% across maize varieties. The highest yield loss was observed in the open-pollinated variety: Arun-2 (34.48%), followed by ZM-627 (20.73%) and BGBY POP (14.85%). The lowest yield loss of 5.54% occurred in RH-12. Application of spinosad 45% EC to RH-12 resulted in increased yield and reduced susceptibility to fall armyworm. These findings suggest that cultivating relatively tolerant maize varieties such as RH-12, combined with appropriate insecticide application, can reduce fall armyworm infestation and yield loss, thereby improving maize productivity and supporting sustainable pest management strategies.